RATE THE EU TO CREATE A «EUROPEAN POLICE CULTURE» - Anatoly K. Kiselev (Вестник Северо-Кавказского федерального университета, 2022)
The article deals two aspects of «police culture» created in the EU: exchange programs and program experience police, anti-corruption work in the police force of the EU.